DESIGN AND IMPLEMENTATION OF VIRTUAL UNIVERSITY BASED ON ICT - Batara, Chris; Rapat, Charnia Iradat (International Journal of Research -GRANTHAALAYAH, 2020)
Virtual University is a learning system by providing an online environment based on information and communication technology. This system can overcome the problems that arise due to covid-19 not to gather together to do the learning process, but must learn from their respective places. This Virtual University system uses Moodle version 3.7 with PHP and MySql programming language platforms as a database server and Apache as a web server can be an innovative learning method that is an ideal solution and in accordance with existing conditions with the hope that it can improve the quality of education if used optimally and comprehensive. This system can perform the basic functions of an e-learning system in which the lecturer can upload lecture material and students can download the material online and can conduct online meetings that can replace face to face in the room. The general objective of this research is to apply a web-based online learning system. The system applied is software that supports the ongoing teaching and learning process for online learning through the internet. The software is installed on the server and can be accessed by participants of online learning programs from browser applications on their PC / cell, and the formation of a university that is not limited by time and space. The stages of this research are: determining user needs, creating a system model, design, system implementation, and testing.